Peran Corporate Governance Terhadap Tax Avoidance pada Perusahaan di Indonesia - Supriatiningsih S; Hidayat Darwis (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2023)
The purpose of this study was to analyze the effect of the audit committee, firm size, leverage and sales growth on tax avoidance. The independent variables used are audit committee, company size, leverage and sales growth. The dependent variable used is tax avoidance. The population in this study are food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The sampling method used is purposive sampling method with a sample of 11 companies during the observation period of 5 consecutive years so that the total sample is 55. The analysis method of this study uses multiple linear regression. Data calculation uses SPSS version 25.The results show that the audit committee and sales growth have no effect on tax avoidance, where the number of audit committees is only to meet government regulations, sales growth where sales growth increases or decreases have the same obligation to pay taxes. Meanwhile, firm size and leverage have a positive effect on tax avoidance